Human papillomavirus-associated head and neck squamous cell carcinoma cells rely on glycolysis and display reduced oxidative phosphorylation - Li, Nora; Chamkha, Imen; Verma, Gaurav; Swoboda, Sabine; Lindstedt, Malin; Greiff, Lennart; Elmér, Eskil; Ehinger, Johannes (Frontiers in Oncology, 2024)
Head and neck squamous cell carcinoma (HNSCC) constitutes a heterogeneous group of cancers. Human papilloma virus (HPV) is associated with a subtype of HNSCC with a better response to treatment and more favorable prognosis. Mitochondrial function and metabolism vary depending on cancer type and can be related to tumor aggressiveness. This study aims to characterize the metabolism of HPV-positive and HPV-negative HNSCC cell lines. Oxidative phosphorylation (OXPHOS) and glycolysis were assessed in intact cells, in four HNSCC cell lines using Seahorse XF Analyzer. OXPHOS was further studied in permeabilized cells using high-resolution respirometry in an Oroboros O2K. Metabolomic analysis was performed using mass spectroscopy. The HPV-negative cell lines were found to display a higher OXPHOS capacity and were also able to upregulate glycolysis when needed. The HPVpositive cell line had a higher basal glycolytic rate but lower spare OXPHOS capacity. These cells were also unable to increase respiration in response to succinate, unlike the HPVnegative cells. In the metabolomic analysis, the HPV-positive cells showed a higher kynurenine/tryptophan ratio. HPV-positive HNSCC preferred glycolysis to compensate for lower OXPHOS reserves, while the HPV-negative HNSCC displayed a more versatile metabolism, which might be related to increased tumor aggressiveness. The higher kynurenine/tryptophan ratio of HPV-positive HNSCC might be related to increased indoleamine 2,3-dioxygenase activity due to the carcinoma's viral origin. This study highlights important metabolic differences between HPV-positive and HPV-negative cancers and suggests that future metabolic targets for cancer treatment should be individualized based on specific tumor metabolism.